1999
DOI: 10.1017/s1360641799002105
|View full text |Cite
|
Sign up to set email alerts
|

Children as Service Evaluators

Abstract: In recent years there has been a growing interest in methods of eliciting children's views on factors influencing their lives. When children's views are sought it is important that this is done in a developmentally appropriate manner with instruments whose psychometric properties are known. The present review describes a variety of methods that have been used to evaluate children's satisfaction with services in education, paediatrics and mental health. The majority of the studies used self-completion qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…A multilayered approach is required to promote the participation of disabled children and young people, which combines listening to them in ways tailored to them as individuals with a recognition that they are consumers of both specialised services and those utilised by their peer group as a whole. Knowledge is available from the specialised studies indicated above and from the larger body of work about participation in decision-making of children as a whole, although even here much development work remains to be done (see, for example, Hennessy, 1999;Dixon-Woods and others, 1999). Both bodies of information provide practitioners and policy makers with examples of innovatory work, but the quality of this evidence is sometimes diminished by a lack of methodological information, for example about sample selection or means of data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A multilayered approach is required to promote the participation of disabled children and young people, which combines listening to them in ways tailored to them as individuals with a recognition that they are consumers of both specialised services and those utilised by their peer group as a whole. Knowledge is available from the specialised studies indicated above and from the larger body of work about participation in decision-making of children as a whole, although even here much development work remains to be done (see, for example, Hennessy, 1999;Dixon-Woods and others, 1999). Both bodies of information provide practitioners and policy makers with examples of innovatory work, but the quality of this evidence is sometimes diminished by a lack of methodological information, for example about sample selection or means of data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Some barriers identified pertain to the complexity and bureaucratic nature of organisations (Matthews, 2001;Kirby and Bryson, 2002, Kirby et al, 2003a, 2003b; to adult attitudes, particularly concerning the capabilities and competence of children, and the need to protect children (Matthews, 2001;Bell et al, 2002;Kirby and Bryson, 2002); to a lack of relevant training and support for adult facilitators and young people participating (Kirby and Bryson, 2002); a lack of research evidence to support participatory activities (Dixon-Woods et al, 1999;Hennessy, 1999); and practical barriers such as time, resources and dedicated funding (NcNeish and Newman, 2002). …”
Section: Barriers To Young People's Participationmentioning
confidence: 99%
“…The need for staff training and skills development in order to promote participation in decision-making by children is highlighted in several studies (Hennessy, 1999;McNeish et al, 2000;Children's Taskforce, Department of Health, 2001;Kirby and Bryson, 2002;McNeish and Newman, 2002;Sloper, 2002, 2003;Kilgour, 2002). Attitudinal changes in health professionals are required about childhood and adolescence, particularly concerning consent and competence (Alderson and Montgomery, 1996);about communication (Beresford and Sloper, 1999); and about the idea of partnership between healthcare professionals and their patients (Bristol Royal Infirmary Inquiry, 2001).…”
Section: Staff Training and Developmentmentioning
confidence: 99%
“…Over the last decades, there has been growing interest in giving students a voice in decision making about factors that influence their lives in school (Hennessy, 1999). Incorporating students' voice into decision making is viewed as a useful and pragmatic practice (Davie & Galloway, 1996) and gives students a sense of ownership (Hennessy, 1999).…”
Section: Students' Voice and The Elementary School Science Curriculummentioning
confidence: 99%
“…Incorporating students' voice into decision making is viewed as a useful and pragmatic practice (Davie & Galloway, 1996) and gives students a sense of ownership (Hennessy, 1999).…”
Section: Students' Voice and The Elementary School Science Curriculummentioning
confidence: 99%